Level of stress among undergraduate, intern and postgraduate medical students measured using perceived stress scale-10: a cross-sectional study - Patil, Harish Sarjerao Maske; Jadhav, Vikas Tukaram; Vhatkar, Pranjali Sukhadeo; Gurav, Ravindra Balaram (International Journal Of Community Medicine And Public Health, 2025)
Background: Medical education both under-graduation and post-graduation is considered as being very stressful now a day and a high level of stress may have a negative impact on cognitive functioning, learning and patient care by the students. So, this cross-sectional study was conducted to determine the prevalence of stress and its determinants among the medical students using perceived stress scale (PSS)-10 scale. Methods: This cross-sectional study was conducted among under-graduate, intern and post-graduate medical students (n=288) of a medical college in Mumbai metropolitan region in the month of June, 2024. PSS-10 scale was used to assess the stress level among the subjects. Data was collected through Google form and analysed by using Microsoft excel. Descriptive and inferential statistics was applied. Statistical significance level was fixed at p<0.05. Results: Google form was submitted to all (n=583) under-graduate, intern and post-graduate medical students of the medical college. The overall response rate among the study subjects was 49.40% (n=288), 67 (44.67%) under-graduates, 30 (60.00%) interns and 42 (47.73%) post-graduates were having very high (PSS-10 score ≥21) stress level. The 26 (49.06%) post-graduate students from clinical and 16 (45.71%) from non-clinical branches were having PSS-10 score ≥21 i.e. very high stress level. The mean PSS-10 score of post-graduates was more (i.e. 23.04±7.24) compared to under-graduate medical students and interns. Conclusions: Perceived stress was high among post-graduate, female and hostelite subjects. More than half of the interns were having very high stress level. Academic burden and family issues were common reasons for perceived stress among the subjects. More research is needed to identify potential confounders.